2021
DOI: 10.3389/fnbeh.2021.689193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Treatment With the NMDA Receptor Antagonist, MK-801, During Different Temporal Windows of Postnatal Period in Adult Prefrontal Cortical and Hippocampal Function

Abstract: The neonatal MK-801 model of schizophrenia has been developed based on the neurodevelopmental and NMDA receptor hypofunction hypotheses of schizophrenia. This animal model is generated with the use of the NMDA receptor antagonist, MK-801, during different temporal windows of postnatal life of rodents leading to behavioral defects in adulthood. However, no studies have examined the role of specific postnatal time periods in the neonatal MK-801 (nMK-801) rodent model and the resulting behavioral and neurobiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…And the performance of male and female Wistar neonatal rats is similar (Faatehi et al, 2019). Treatment of C57BL/6 neonatal mice with low concentrations of MK-801, such as 0.1 mg/kg, has similar effects (Plataki et al, 2021). However, it has also been argued that chronic MK-801 administration induces working memory deficits in NOR with a threshold of administration concentration, and only concentrations higher than 0.5 mg/kg can successfully induce working memory deficits (Murueta-Goyena et al, 2018).…”
Section: Mk-induced Cognitive Impairment In Rodents With Schizophreniamentioning
confidence: 98%
See 1 more Smart Citation
“…And the performance of male and female Wistar neonatal rats is similar (Faatehi et al, 2019). Treatment of C57BL/6 neonatal mice with low concentrations of MK-801, such as 0.1 mg/kg, has similar effects (Plataki et al, 2021). However, it has also been argued that chronic MK-801 administration induces working memory deficits in NOR with a threshold of administration concentration, and only concentrations higher than 0.5 mg/kg can successfully induce working memory deficits (Murueta-Goyena et al, 2018).…”
Section: Mk-induced Cognitive Impairment In Rodents With Schizophreniamentioning
confidence: 98%
“…For example, C57BL/6 neonatal mice show impaired discrimination index when MK-801 is administered on postnatal days 7–14, but there is no significant difference in NOR results between MK-801 treated and control mice when MK-801 is administered on postnatal days 11–15. This suggests that there is a time window for the effect of MK-801 on cognitive function (Plataki et al, 2021 ). In addition, acute MK-801 treatment also reduces the discrimination index of male C57/BL6J mice (Prades et al, 2017 ).…”
Section: Mk-801 Induced Cognitive Impairment In Rodents With Schizoph...mentioning
confidence: 99%
“…The early-life or adolescent blockade of NMDA receptors induced the schizophrenia-like behavioural response in adult animals [ 102 ]. Biochemical studies have shown that behavioural changes are related to the alterations in histone acetylation (H3K9ac) [ 103 ] or in HDAC5 levels in the adult PFC of animals with postnatal blockade of NMDA receptors [ 103 , 104 ].…”
Section: Aetiology Of Schizophreniamentioning
confidence: 99%
“…Multiple studies have shown that administration of sub‐anesthetic doses of ketamine and PCP can induce a spectrum of schizophrenia‐like symptoms including psychosis and neurocognitive disturbances in healthy individuals, and exacerbate symptoms in people with schizophrenia (Allen & Young, 1978; Cheng et al, 2018; Krystal et al, 1994; Lahti et al, 1995; Luby et al, 1959; Xu et al, 2015). In rodents, administration of these NMDAR channel blockers results in hyperlocomotion (proposed to represent a striatal hyperdopaminergic state which is thought to underlie the positive symptoms of schizophrenia like psychosis), disruption of the prepulse inhibition of the startle response, and cognitive deficits as assessed by various behavioral tests including the T‐maze and object recognition tasks (Cadinu et al, 2018; Gigg et al, 2020; Neill et al, 2014; Plataki et al, 2021; Sahin et al, 2016; Suryavanshi et al, 2014; Usun et al, 2013). Multiple studies have reported that GluN2D knockout (KO) mice are resistant to NMDAR antagonist‐induced hyperlocomotion, thus suggesting a role for the GluN2D subunit in mediating psychotomimetic drug‐induced hyperlocomotor behavior (Hagino et al, 2010; Ikeda et al, 1995; Sapkota et al, 2016; Yamamoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%